¿Armas o herramientas prehistóricas?: el ejemplo del mundo argárico - Sanahuja Yll, Mª Encarnación (Complutum, 2007)
In this paper the definition of weapon is analysed, not only because ethnographic and contemporary visions have been used in order to classify them, but because the social interpretation we can infer about these artefacts are quite different, taking into account the explanation as a tool or as a weapon. The only way to progress is in one hand, the use of functional analysis on metal objects in order to know their technological conditions and their social and economic implications; in other hand, we must consider several data (artefacts, human bones, settlement) in a geographic area in order to confirm the existence of violent confrontations or war. As an example, copper and bronze tools from the Argar Culture will be analysed.